Krisis Legitimasi dan Erosi Kepercayaan: Analisis Rendahnya Partisipasi dalam Kepemimpinan Organisasi Mahasiswa - Temmar, Edwin; Telussa, Sandra; Tahalele, Olivia (Universitas Pattimura, 2024)
This study investigates a legitimacy crisis and erosion of trust in student organization leadership by examining declining participation as a critical indicator of internal dysfunction. Focusing on the Indonesian Christian Student Movement (GMKI) Ambon Branch, the research explores how organizational communication failures contribute to weakened leadership credibility. Employing a qualitative methodology, data were collected through observations and in-depth interviews with both members and organizational leaders. Grounded in Stephen P. Robbins’ organizational communication theory, the analysis highlights the breakdown of vertical and horizontal communication, lack of message clarity, weak interpersonal relationships, and the absence of responsive feedback systems. These issues foster psychological distance between leaders and members, diminishing trust and organizational identification. Moreover, strategic ambiguity and value fragmentation further accelerate symbolic delegitimization of leadership, leading to apathy and minimal engagement among members. The novelty of this study lies in its integration of organizational communication theory into the context of student leadership, offering a unique lens to interpret participation decline not merely as behavioral disengagement but as a symptom of deeper structural and symbolic fractures. This research suggests that revitalizing student organizations requires inclusive, dialogical communication models that restore trust and participatory legitimacy in leadership.